Peran Posyandu Mendukung Integrasi Layanan Primer Untuk Mencegah Anemia Pada Kehamilan Di Puskesmas Berbah - Mutiara, Julita; Diniyah, Kharisah (Midwifery Care Journal, 2025)
Â Anemia during pregnancy is often referred to as a "potential danger to mother and child," meaning it poses a significant risk to both. The effects of anemia during pregnancy include hemorrhage, miscarriage, and preterm birth. In fetuses, it can lead to neonatal death, low birth weight, and heart disease. In Indonesia, the prevalence of anemia is 48.9%. Pregnant women are advised to consume at least 90 iron (Fe) tablets throughout pregnancy. Proper consumption of iron tablets involves avoiding tea and coffee while taking them, as these beverages can inhibit iron absorption. Factors influencing anemia include compliance with iron tablet consumption and the frequency of antenatal care visits. This study aims to examine the role of Posyandu (Integrated Health Post) in supporting the integration of primary healthcare services to prevent anemia during pregnancy. It employed qualitative research method and involved research participants, including key informants (midwives and health cadres) and supporting informants (pregnant women). Data were collected using a purposive sampling technique and in-depth interviews, with interview guidelines and a voice recorder as research instruments. Data analysis followed several stages: data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that Posyandu plays a crucial role in preventing anemia during pregnancy at Puskesmas (Community Health Center) Berbah. Its roles include encouraging antenatal care visits, promoting Posyandu attendance, providing health and nutrition education, detecting anemia risk early among pregnant women, referring cases to healthcare facilities, and monitoring behavioral compliance.